SELECTION CRITERIA AND ALGORITHM FOR THE USE OF HIGH-INTENSITY INTERVAL TRAINING IN PATIENTS AFTER STROKE - Vinohradov, M. M.; Lazarieva, O. B. (Rehabilitation and Recreation, 2023)
Objective – to determine the main criteria for involving patients with acute cerebrovascular accident in high-intensity interval training as part of complex physical therapy in the conditions of a multidisciplinary team. Material and Methods: analysis of scientific and methodological literature; medical observations; determination of the safety of integration of high-intensity interval training based on the assessment of heart rate, blood pressure, state of health according to the Borg scale and close cooperation with doctors of a multidisciplinary team, namely cardiologists and neurologists. Results. Based on the results of observations and a review of scientific and methodological literature, the effectiveness of high-intensity interval training as a component of complex physical therapy was substantiated. In the correct mode of use, it is possible to clearly define the basic conditions for the safe involvement of patients in this type of training. The main conditions are: an adequate response of the cardiorespiratory system to exercise, stable patient condition, no contraindications to mobilization, permission of a specialized physician, namely a cardiologist and a neurologist, cognitive preservation and the ability to adequately assess the patient’s well-being, a built-in algorithm for communication with the patient and the use of feedback models focused on subjective and objective components. The use of an approbation period to determine the feasibility and safety of including a patient in high-intensity training is described. Conclusions. The use of high-intensity interval training is very common and effective abroad, which is confirmed by a large number of specialized scientific and methodological literature. The importance of proper communication among a multidisciplinary team is the main component on which the algorithm for selecting patients for the use of high-intensity training in Ukraine is based. The issue of using this type of training in Ukraine does not have significant scientific and methodological research and requires more study and integration.